Implementation of Discharge Planning in Patients with Moderate Brain Injury in Inpatient Rooms: Pelaksanaan Discharge Planning Pada Pasien Cedera Otak Sedang di Ruang Rawat Inap - Pitaloka, Dyah Ayu; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhamad; Sri W, Indah (Al-Hijrah Indonesia, 2022)
Implementation of Discharge Planning in Patients with Moderate Brain Injury in the Inpatient Room, Jember District Hospital. Discharge planning is an interaction process that occurs in multidisciplinary health workers, patients and their families who collaborate in providing and planning the continuity of care needed by patients. The purpose of this scientific work is to determine the implementation of discharge planning by nurses in the Inpatient Room. This writing method used a descriptive observational case study method. In this scientific work, it was found that discharge planning was carried out immediately after the patient entered and when the patient was going home. The implementation was done collaboratively and adapted to existing resources and facilities. The activity had been structured and carried out properly in accordance with the SOP and written on the discharge planning sheet of the room. It was concluded that the implementation of discharge planning in the Inpatient Room was carried out properly and in accordance with existing theories, so that the quality of nursing services could increase. Therefore, it was recommended that nurses in the treatment room could carry out discharge planning properly so that the nursing care provided would be higher quality.